Inclusive Education Status through the Lenses of Teachers in Zambia - Kenneth Kapalu Muzata; Francis Simui; Dikeledi Mahlo; Phydes Ng'uni (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2021)
This study was conducted to examine the status of inclusive education in Zambia, learning from teachers' perspectives about how inclusive education is being implemented and the whether teachers receive adequate support to implement inclusive education to learners with disabilities. The study employed a concurrent mixed design approach in which both quantitative and qualitative data were generated and applied. Open and closed ended questionnaires were used to collect data from teachers that were upgrading their qualifications via distance education at Kwame Nkrumah University, University of Zambia and Chalimbana University. Findings indicated that Zambia practices partial inclusion in which only the mild and moderate learners with disabilities are included in classrooms. Inclusive education is understood by teachers in the context of disability and teachers reported that they did not receive adequate support to implement inclusive education effectively. It is recommended that the Government of the Republic of Zambia through the Ministry of General Education should focus on training teachers in inclusive education and its methodologies to meet the learning needs of learners from different circumstances